PROTOTYPE SECURITY SYSTEM OPENS DOORS WITH TELEGRAM BOT INTERNET-BASED OF THINGS - Tri Sakti; Imam Suharjo (Universitas Teknokrat Indonesia, 2021)
AbstrakTechnological advances today are very developed, so it can help the community in monitoring home security. One example is offices or houses owned by themselves. In this research I am interested in doing research and development in the field of IoT where this research aims to build a system that can help homeowners to provide security at the door of the house during remote travel. With fingerprint system equipped with door monitoring using botTelegram this system itself is implemented with the concept of internet of things (IoT). In this study using the concept of internet of things implemented in the automatic door system using microcontroller that serves as a prototype regulator so that the prototype can run properly. In this system has an interface in the form of Telegram-based applications by utilizing BotTelegram that serves as a communication tool between users and the system. In this system, users can monitor the security of the door when traveling or at home. Based on the results of the study, it can be concluded that the system can run with a percentage of 85% where the system can open automatic doors with fingerprint configuration data that has been registered in the fingerprint module. Keywords: Internet of things, fingerprints, telegram bots, nodemcu, Door Security